2016
DOI: 10.1073/pnas.1615400113
|View full text |Cite
|
Sign up to set email alerts
|

Targeted molecular-genetic imaging and ligand-directed therapy in aggressive variant prostate cancer

Abstract: Aggressive variant prostate cancers (AVPC) are a clinically defined group of tumors of heterogeneous morphologies, characterized by poor patient survival and for which limited diagnostic and treatment options are currently available. We show that the cell surface 78-kDa glucose-regulated protein (GRP78), a receptor that binds to phage-display-selected ligands, such as the SNTRVAP motif, is a candidate target in AVPC. We report the presence and accessibility of this receptor in clinical specimens from index pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 53 publications
3
31
0
Order By: Relevance
“…Attesting to its inherent versatility, ligand-directed AAVPbased delivery of transgenes in preclinical settings has been demonstrated successfully in xenograft and transgenic models of soft-tissue sarcomas (10), glioblastomas (11), and neuroendocrine pancreatic tumors (12), in addition to the original new technology report in breast and prostate cancer in tumor-bearing mice a decade ago (9,19). Notably, one also could speculate that the described ligand-directed theranostic approach introduced here could also be used to determine the precise location of a lesion intraoperatively and/or to integrate the administration of tumor-directed treatments based on the recent report of an enabling AAVP-based nanotechnology platform (46). (See SI Discussion for a further discussion of the potential for AAVP in the clinical setting.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Attesting to its inherent versatility, ligand-directed AAVPbased delivery of transgenes in preclinical settings has been demonstrated successfully in xenograft and transgenic models of soft-tissue sarcomas (10), glioblastomas (11), and neuroendocrine pancreatic tumors (12), in addition to the original new technology report in breast and prostate cancer in tumor-bearing mice a decade ago (9,19). Notably, one also could speculate that the described ligand-directed theranostic approach introduced here could also be used to determine the precise location of a lesion intraoperatively and/or to integrate the administration of tumor-directed treatments based on the recent report of an enabling AAVP-based nanotechnology platform (46). (See SI Discussion for a further discussion of the potential for AAVP in the clinical setting.…”
Section: Discussionmentioning
confidence: 84%
“…Gene therapy has been recognized as a great promise for the treatment of cancer, but the lack of a robust system to deliver reporter and/ or therapeutic transgene(s) effectively and specifically is a serious limiting factor. The AAVP-based strategy reported here has its maximum diagnostic and therapeutic efficacy targeted at the tumor site, making it a promising candidate for the development of first in-human clinical trials for tumors such as IBC and aggressive variant prostate cancer (46), which are in the advanced planning stage. Finally, in the future other tumor-specific ligandreceptor systems and/or inducible promoters may be integrated easily into the AAVP-based platform.…”
Section: Discussionmentioning
confidence: 99%
“…The other recent therapeutic model utilized a phage, displaying a ligand specific to GRP78, to deliver the herpes simplex virus thymidine kinase type-1 suicide inducing transgene to mice with MDA-PCa-118b patient derived tumor xenografts. After treatment with the antiviral drug ganciclovir, tumors were reduced by an average of 50%[33]. It is curious to speculate whether ionizing radiation could be employed prior to treatment with the viral phage to upregulate expression of GRP78 to increase the effectiveness of phage targeting of cancer cells.…”
Section: Stem Cells and Er Stressmentioning
confidence: 99%
“…The aim of gene therapy is to transfect a target gene into host cells to be specifically expressed, thus killing tumor cells. Currently, suicide gene therapy has become a promising strategy for gene therapy, especially the herpes simplex virus thymidine kinase ( HSVtk )/ganciclovir (GCV) system (10). Previous studies have demonstrated the use of a pro-drug sensitive gene as a suicide gene, to convert a non-toxic pro-drug into a toxic product, to block the extension of DNA chains and inhibit the activation of DNA polymerase, finally leading to cell apoptosis (1113).…”
Section: Introductionmentioning
confidence: 99%